The role of the World Bank in reducing extreme poverty in some Arab countries - زيود لين; لؤي صيوح; عبير ناعسة (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The research aimed to shed light on the problem of poverty in some Arab countries, in particular, that the General Assembly of the United Nations, by its resolution 1 A/RES/70 in 2015, confirmed the achievement of a better percentage of the goal of eradicating extreme poverty, as it planned to reduce it to 3% Until the year 2030, knowing that the number of the extremely poor decreased from 1.9 billion in 1990 to 987 million in 2015, or by 48%. The research also aimed to shed light on the role of the World Bank in reducing extreme poverty, as it has a responsibility to partially contribute to financing sustainable development projects in developing countries. . The researcher linked the goal of eradicating extreme poverty to the extent to which the World Bank loans achieved indicators of the economic dimension of sustainable development in the studied Arab countries, including: the growth of the per capita share of the gross domestic product, and the percentage of capital formation. Her hypotheses were tested by simple regression analysis, and she reached the following results: The high population growth rate in Egypt and Jordan is a real obstacle and challenge to them, which reduces the possibility of reducing extreme poverty in them. The World Bank loans to Egypt and Morocco did not contribute to increasing the per capita share of the Egyptian or Moroccan GDP, nor did they increase their capital formation, nor did they lead to reducing the percentage of the extreme poor in them. The loans of the World Bank to Jordan contributed to increasing the Jordanian per capita share of the GDP, while these loans did not show an impact on the value of its capital formation, and were accompanied by a very small rate of extreme poverty, but they brought it to a critical degree of indebtedness, and posed a challenge and threat his development.